2023
DOI: 10.1016/j.prosdent.2021.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic on anxiety in patients with masticatory muscle pain

Abstract: Statement of problem Although psychological disorders have been established as one of the etiological factors for temporomandibular disorders, anxiety levels in individuals with masticatory muscle pain before and during the coronavirus 2019 (COVID-19) pandemic have not previously been compared. Purpose The purpose of this clinical study was to evaluate anxiety levels in patients with masticatory muscle pain at times before and during the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…In a study conducted with patients who suffered from pain in the masticatory muscles, anxiety levels were measured before and after the COVID 19 pandemic using the Generalized Anxiety Disorder 7 (GAD-7) questionnaire. Anxiety levels rose during the pandemic [14], and this also happened among the participants of the study who reported high levels of stress due to multiple causes such as losing their jobs or being in lockdown. It has been determined that circumstances such as being under high levels of psychological stress, and muscular overload, lead to the development of one or more muscle bands on which there may be a latent trigger point [15].…”
Section: Discussionmentioning
confidence: 80%
“…In a study conducted with patients who suffered from pain in the masticatory muscles, anxiety levels were measured before and after the COVID 19 pandemic using the Generalized Anxiety Disorder 7 (GAD-7) questionnaire. Anxiety levels rose during the pandemic [14], and this also happened among the participants of the study who reported high levels of stress due to multiple causes such as losing their jobs or being in lockdown. It has been determined that circumstances such as being under high levels of psychological stress, and muscular overload, lead to the development of one or more muscle bands on which there may be a latent trigger point [15].…”
Section: Discussionmentioning
confidence: 80%
“…Categorical variables were described as counts ( n ) and percentages (%). The questionnaire scores were expressed as mean ± SD, and between-group statistical comparisons were made using an independent sample t -test or the Mann-Whitney U test, depending on normal distribution ( 25 , 26 ). Two-sided P -values were considered significant at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…15 Birçok çalışmada TMD'e sahip hastaların OHIP-14 ve GAD-7 anket sonuçları değerlendirilmiştir. [16][17][18] Ancak bu çalışmalarda yalnızca çiğneme kas hastalığına sahip TMD vakaları izole edilmemiş, ayrıca eğitim durumu ve meslek durumuna göre karşılaştırma yapılmamıştır. Bu çalışmanın amacı, yalnızca çiğneme kası ağrısına sahip TMD hastalarının ağız sağlığını değerlendiren OHIP-14 anketi ile GAD-7 anket puanlanma sonuçlarını cinsiyet, eğitim durumu ve mesleki duruma göre karşılaştırmak ve yaş…”
Section: Hastalarınunclassified
“…GAD-7, 0 (hiç), 1 (birkaç gün), 2 (günlerin yarısından fazlası), 3 (hemen hemen her gün) olmak üzere 7 madde ve 4 cevap seçeneği içermektedir. 0 ile 21 arasında değişen toplam puanlar, her bir maddeye verilen cevapların aritmetik toplamı ile hesaplanmış ve 16 minimal (0-4), hafif (5-9), orta (10)(11)(12)(13)(14) ve şiddetli (15)(16)(17)(18)(19)(20)(21) olmak üzere orijinal forma göre dört alt gruba ayrılmıştır.…”
Section: Gereç Ve Yöntemunclassified